Microbial community analysis of fouled reverse osmosis membranes used in water recycling - Ayache, C.; Manes, C.; Pidou, M.; Croué, Jean-Philippe; Gernjak, W. (IWA Publishing, 2013)
Biofouling on RO membranes has major cost implications in water reclamation. In this study membranes and water samples were collected from a RO pilot-plant operated on two sites to study the differences in microbial communities in order to develop a better understanding of the biofouling. For the two sites studied, the examination of the front membrane of the first stage and the tail membrane of the second stage of the RO train using 16S rRNA gene-based molecular technique showed that bacteria were similar on both stages and no significant effect of the membrane location within the RO train on the biofilm development could be discerned. However, the comparison of the identified bacteria from membrane samples between the two sites showed that each site is specific, leading to a different composition of microbial communities. The different nutrient concentrations in the RO feed water due to the different biological pre-treatments are one potential explanation for the observed differences in the microbial communities. Seasonal variations also play a major role in the development of microbial communities as shown by the significant differences observed between the communities measured in the samples in winter and summer on the second site. The results did not show similarity between the species identified on the RO membranes and in the feed water. Hence, the relationship of microbial community between the water generated during the pre-treatment process and RO membranes is not obvious. From this study, results showed that there is an actual need to investigate the development of microbial communities on membrane surface in real conditions in order to suggest tailored solutions for biofouling control and removal.